Intestinal duplicity with ultrasound diagnosis. A case report - Diana García Rodríguez; Yisel González Ríos; Leidelén Esquivel Sosa; Abel Armenteros García (Medisur)
Intestinal duplication is a rare condition that is diagnosed and resolves within the first two years of life. They can be diverticular, cystic or tubular, communicating and non-communicating. The symptoms vary with the type, size, location and mucosa that covers them. This research aims to present the case of a pediatric patient diagnosed with ileal intestinal duplication, in which imaging tests contributed to the definitive diagnosis. This is a 16-month-old female patient who presented with diffuse, intermittent colicky abdominal pain, bloody stools, abdominal distention, and irritability. A simple abdominal X-ray revealed distention of the intestinal loops, such as air-fluid levels and the presence of gas in the rectum. Ultrasound revealed a cystic image towards the right hypochondrium, in close contact with the adjacent intestinal loop, double wall sign and fluid-fluid level. The diagnosis of ileal intestinal duplication was suggested, which was confirmed with a biopsy after surgery. Ultrasound is the test of first choice in the diagnosis of this condition. It shows the double wall sign with an inner echogenic layer (epithelium) and an outer hypoechoic layer corresponding to the muscle layers. The methods of imaging studies are of vital importance for its diagnosis, it is the abdominal ultrasound that provides an accurate diagnosis, being harmless for the patient.